A2_4 American Atlantis - Perks, Megan; Stylianou, Natalia; Filip, Tom; McMullan, Mac (Physics Special Topics, 2021)
This article assesses the impact on global sea levels if some of America's major coastal cities were to be submerged in giant underwater domes to protect them from flooding due to global warming. It was found that by submerging New York, Los Angeles, Boston, Washington DC, San Francisco, Seattle and Miami, global sea levels would only rise by 3.61x10^-3 m (or 0.361 cm.)